Telaah Jenis Makna Poster Unjuk Rasa dan Relevansinnya Sebagai Diktat Teks Argumentasi - Salsabila, Salsabila; Syafroni, Roni Nugraha; Setiawan, Hendra (Prawara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Language functions not only as a means of communication but also as a persuasive and expressive tool capable of influencing people's mindsets and attitudes. One powerful manifestation of language utilization is in demonstration posters, which are often imbued with denotative and connotative meanings. This study aims to analyze these types of meanings in a demonstration poster titled "Dark Indonesia" that went viral on social media in February 2025. The approach used was qualitative with descriptive methods, where data from 15 posters were analyzed based on Abdul Chaer's semantic theory. The results showed that 10 posters contained connotative meanings, while the other 5 contained denotative ones. Connotative meanings tend to be used to convey social criticism emotionally and persuasively, while denotative meanings emphasize straightforward presentation of facts. These findings indicate that demonstration posters function not only as a medium for criticism but also have potential as contextual teaching materials in Indonesian language learning, particularly in writing argumentative texts in grade 11. Therefore, the results of this study are relevant in the form of teaching materials to improve students' critical thinking and argumentative skills through language analysis in real contexts.